Application Research of Data Encryption Technology in Computer Network Security - Li, Siying (Procedia computer science, 2025)
Under the social background of the rapid development of information technology and Internet technology, computer network provides convenient conditions for people’s data transmission work, so that the work has broken through the restrictions of time and space, but at the same time it also brings illegal invasion, virus damage, information leakage and other network security problems. Based on this, this paper expounds the meaning and algorithm of data encryption technology, focuses on the analysis of common data encryption technology, in order to comprehensively improve the application of data encryption technology, effectively avoid all kinds of network security problems, build a safe network communication environment, and promote the development of computer network communication in China.